2023
DOI: 10.1126/sciadv.adf6138
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the secret of ancient Maya masons: Biomimetic lime plasters with plant extracts

Abstract: Ancient Maya produced some of the most durable lime plasters on Earth, yet how this was achieved remains a secret. Here, we show that ancient Maya plasters from Copan (Honduras) include organics and have a calcite cement with meso-to-nanostructural features matching those of calcite biominerals (e.g., shells). To test the hypothesis that the organics could play a similar toughening role as (bio)macromolecules in calcium carbonate biominerals, we prepared plaster replicas adding polysaccharide-rich bark extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“… 135 Inspiration in designing novel sustainable materials with enhanced properties can also come from ancient civilizations and cultures, where nanomaterials and interfacial phenomena were exploited based on empirical knowledge. Examples include archeological or paleontological materials that survived to recent times, 136 or the enhanced properties of Maya plasters (that mixed biomacromolecules in calcium carbonate biominerals) 137 and Roman cement. 138 With today’s awareness and scientific understanding of colloidal and interfacial processes, the time thus is ripe for a new, sustainable breakthrough in the preservation of works of art.…”
Section: Discussionmentioning
confidence: 99%
“… 135 Inspiration in designing novel sustainable materials with enhanced properties can also come from ancient civilizations and cultures, where nanomaterials and interfacial phenomena were exploited based on empirical knowledge. Examples include archeological or paleontological materials that survived to recent times, 136 or the enhanced properties of Maya plasters (that mixed biomacromolecules in calcium carbonate biominerals) 137 and Roman cement. 138 With today’s awareness and scientific understanding of colloidal and interfacial processes, the time thus is ripe for a new, sustainable breakthrough in the preservation of works of art.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Navarro et al have shown that, most likely without knowing, the Mayas masons used a biomimetic strategy to produce superior binders involving the incorporation of organics in between and inside the calcite crystals (Figure ). This gave the mortar a plastic behavior and a higher toughness while increasing its resistance to weathering processes . This biomimetic approach is really promising for improving the properties of CASC.…”
Section: Crystallization Of Hydrated Phases In Alternative Bindersmentioning
confidence: 98%
“…In addition to exerting polymorphic control, the occlusion of organics within the carbonated products could be exploited to create biomimetic organic–inorganic hybrid structures, which exhibit superior mechanical performance compared to pure calcium carbonate phases (see Section ). Interestingly, this phenomenon has been observed in the lime-based mortars of Copán (Honduras), relics of ancient Mayan craftsmanship, which stand out as some of the most durable lime plasters on the planet . There is evidence that Maya masons used plant extracts rich in polysaccharide, that could be the key behind the incredible durability of their lime-based materials.…”
Section: Crystallization Of Hydrated Phases In Alternative Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopolymers extracted from cactus plants, rice (amylopectin), and tree bark are considered "traditional natural materials", and their use has transcended generations through oral information and local practice, which has allowed for their biotechnological application in the field of conservation and restoration [5][6][7]. Recently, Rodriguez-Navarro and coworkers [8], using a multidisciplinary approach, elegantly demonstrated that polysaccharide-rich bark extracts from Mayan trees contributed to the production of a calcite cement with meso-to-nanostructural features, matching those of calcite biominerals (e.g., shells). These authors proved the hypothesis that organics (biopolymers) could play a similar toughening role as (bio)macromolecules in calcium carbonate biominerals.…”
Section: Introductionmentioning
confidence: 99%